How motivation to work affects nursing service quality according to the perception of registered nurses at Phyathai hospital group in Bangkok, Thailand - Thiengburanatham, Ubonwan; Intraraprasong, Pusita; Kaewpan, Wanpen; Sillabutra, Jutatip (Journal of Public Health and Development, 2011)
This research aims to explain work motivation that affects nursing service quality according to the perception of registered nurses at Phyathai Hospital Group. There were a total of 199 nurses. Research tools used were questionnaires regarding nursing service quality and work motivation according to the perception of registered nurses. The hypothesis was tested by analyzing relationships using Pearsons' product moment correlation and by analyzing the ability to explain the variance of nursing service quality according to the perception of registered nurses using multiple linear regression. Results showed that nursing service quality according to the perception of registered nurses at Phyathai Hospital Group was at a very good level. Work motivation of registered nurses at Phyathai Hospital Group was at a good level and had a positive relationship with nursing service quality according to the perception of registered nurses. Motivation factors had a moderate positive relationship but hygiene factors had a low level positive relationship with nursing service quality according to the perception of registered nurses. Motivation factors and hygiene factors could predict 97.6% of nursing service quality. This research recommends that management should provide more support in terms of policy and administration by improving relationships among peers, recognition, possibility of growth, responsibility, advancement, relationship with subordinates, work itself, salary, working conditions and supervision-technical that will result in the development of nursing service quality.